2020
DOI: 10.1111/exd.14092
|View full text |Cite
|
Sign up to set email alerts
|

Beyond antibodies: B cells in Hidradenitis Suppurativa: Bystanders, contributors or therapeutic targets?

Abstract: Hidradenitis Suppurativa (HS) is a chronic inflammatory dermatosis in which B cells play a prominent but unclear role. Our understanding of the role of B cells in innate and adaptive immunity (including antibody production, antigen presentation and effector functions) is rapidly evolving; and these novel findings require integration into the pathophysiologic model of HS. B cells are transiently present in normal human skin and have functions in the maintenance of innate cutaneous immunity. Recruitment and traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…However, to date no product has been definitively identified as an autoimmune target for the disease. 83 B cells are present in other chronic inflammatory disorders without known Initiating factors in hidradenitis suppurativa. Normal control skin (first panel from the left) from hidradenitis suppurativaeassociated cutaneous sites (eg, axilla) have normal colonizing microbionts (including within the follicular infundibulum), which are continuously monitored by circulating immune cells in homeostasis (circulating to and from regional lymph nodes (inset in first panel from the left).…”
Section: The Role Of B Cells Despite Their Dominance Remains Unclearmentioning
confidence: 99%
See 4 more Smart Citations
“…However, to date no product has been definitively identified as an autoimmune target for the disease. 83 B cells are present in other chronic inflammatory disorders without known Initiating factors in hidradenitis suppurativa. Normal control skin (first panel from the left) from hidradenitis suppurativaeassociated cutaneous sites (eg, axilla) have normal colonizing microbionts (including within the follicular infundibulum), which are continuously monitored by circulating immune cells in homeostasis (circulating to and from regional lymph nodes (inset in first panel from the left).…”
Section: The Role Of B Cells Despite Their Dominance Remains Unclearmentioning
confidence: 99%
“…Byrd et al 3 demonstrated that antibodies to citrullinated peptides contribute to the development of neutrophil extracellular traps in advanced disease, with parallels to B-cell and neutrophil extracellular traps in rheumatoid arthritis. 3 Case reports of rituximab ameliorating hidradenitis suppurativa disease activity are known, 83 but overall, the role of B cells as bystanders, amplifiers of existing inflammation, or central pathogenic players is unclear and requires further investigation. 83 The inflammatory infiltrate is associated with high levels of matrix metalloproteinases, which degrade the reticular lamina.…”
Section: The Role Of B Cells Despite Their Dominance Remains Unclearmentioning
confidence: 99%
See 3 more Smart Citations